Enhanced biocidal efficacy of alcohol based disinfectants with salt additives - Euna Oh; Hyerin Shin; Sumin Han; Soo Jee Do; Younseo Shin; Ji Hee Pi; Youngjin Kim; Dae-Hong Ko; Kyu Hyoung Lee; Hyo-Jick Choi (Scientific Reports)
Abstract Surfaces contaminated with pathogens pose a significant risk of disease transmission and infection. Alcohol-based disinfectants are widely utilized to decontaminate high-touch areas across various settings. However, their limited antimicrobial activity and the emergence of alcohol-tolerant strains necessitate the development of highly efficient disinfectant formulations. In this work we test the broad-spectrum antimicrobial activities of the salt-incorporated alcohol solution disinfectant against enveloped and non-enveloped viruses, spore-forming and non-spore-forming bacteria, and mold and yeast fungi. Specifically, the disinfection capability of the isopropanol (IPA) and ethanol (EtOH) solutions containing NaCl salts was evaluated by measuring (1) antibacterial activity against Gram-positive bacteria (methicillin-resistant Staphylococcus aureus), Gram-negative bacteria (Pseudomonas aeruginosa, Escherichia coli), and an alcohol-tolerant strain of E. coli; (2) sporicidal activity against Clostridioides difficile; (3) the antiviral activity against enveloped A/PR8/34 H1N1 influenza virus and non-enveloped adenovirus VR-5; and (4) the antifungal efficacy against Aspergillus niger and Cryptococcus neoformans from the time-dependent viability assays. Additionally, the biocidal activity of the disinfectant formulation was tested by spraying it on the biocontaminated surfaces, including plastics, stainless steel, and glass. Overall, the inclusion of salt in alcohol solutions significantly enhanced their disinfection activities, positioning these solutions as promising candidates for long-term disinfection and maintenance of hygienic environments. This method, which employs mild salt instead of toxic materials, offers a simpler, more cost-effective, and safer alternative to conventional alcohol-based disinfectants. This research is expected to significantly impact on disease prevention and contribute greatly to public health and safety.